2016
DOI: 10.1002/adhm.201600717
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of Superhemophobic Titania Surfaces

Abstract: The hemocompatibility of superhemophobic surfaces is investigated and compared with that of hemophobic surfaces and hemophilic surfaces. This analysis indicates that only those superhemophobic surfaces with a robust Cassie-Baxter state display significantly lower platelet adhesion and activation. It is envisioned that the understanding gained through this work will lead to the fabrication of improved hemocompatible, superhemophobic medical implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 52 publications
1
69
0
Order By: Relevance
“…The solid surface energies were determined to be approximately 40 mN/m for Ti and NT, 11 mN/m for NT-S1, and 50 mN/m for NT-S2 through Owens-Wendt analysis, which are consistent with previously published data on titania nanotube arrays. [15,37,40]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid surface energies were determined to be approximately 40 mN/m for Ti and NT, 11 mN/m for NT-S1, and 50 mN/m for NT-S2 through Owens-Wendt analysis, which are consistent with previously published data on titania nanotube arrays. [15,37,40]…”
Section: Resultsmentioning
confidence: 99%
“…[6] The adhered bacteria were fixed using a process described elsewhere. [40,41] In brief, the surfaces were soaked in a primary fixative made of 0.1 M sucrose, 0.1 M sodium cacodylate, and 3% glutaraldehyde (v/v) in DI water for 45 mins. The surfaces were then moved to the secondary fixative composed of 0.1 M sucrose and 0.1 M sodium cacodylate in DI water.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, platelet adhesion can be reduced by limiting the effective area available to platelets (Figure a). One way to limit the effective area is to utilize a superhydrophobic surface in the Cassie state . Movafaghi et al showed that superhydrophobic titania nanotubes reduce the number of adherent platelets by up to 67% compared to nontextured surfaces, which was explained by a stable Cassie state leading to a smaller effective area.…”
Section: Micro‐ and Nanostructure‐induced Blood‐repellencymentioning
confidence: 99%
“…[39,42,43] Superhydrophobic surfaces can be systematically designed by combining low solid surface energy with appropriate microscale or nanoscale texture. [44][45][46][47][48][49][50][51][52] While textured superhydrophobic surfaces can prevent the accumulation of water and help retain the dielectric strength of insulators under wet conditions, the presence of texture reduces the dielectric strength due to the accumulation of charge on sharp features. [53][54][55] In this work, we investigated whether or not textured superhydrophobic surfaces can retain the dielectric strength under wet conditions.…”
Section: Superhydrophobic Insulatorsmentioning
confidence: 99%
“…A surface is considered to be superhydrophobic if it displays θ * > 150° and Δθ * < 10° with water . Superhydrophobic surfaces can be systematically designed by combining low solid surface energy with appropriate microscale or nanoscale texture …”
mentioning
confidence: 99%